(untitled) (Eduscotech, 2023)
This research is aims to improve the spirit in prcticing bdminton sport using shuttlecock. The subjects of this study were the ebginner athletes aged 7-10 years at PB. Putra Mustika Blora. This typ of research is comprised of potentials and issues of information collection, product design, design validation, design improvements, product trials, trial usage, and mass product manufacturing. The results showed that the development of agility exercise positive impact, this is evident from the end of the research given repeatedly, and the result of research that is the result of quentionnaire likert scale 100%.